Risālah-yi zubdat al-mufradāt-i manẓūm, maʿa risālah-yi dalāʼil-i nabz̤ va baul mulaqqab bah Naẓm-i bāriq - Malīḥ, Sayyid ʿAlī Ḥasan (Munšī Naval Kišor, 1884)
Two medical treatises in verse, the one on materia medica, the other on the pulse and urinary diseases